Comparison of clonidine and dexmedetomidine as an adjuvant to bupivacaine in supraclavicular brachial plexus block for upper limb orthopedic procedures - Kirubahar, Rajaclimax; Sundari, Bose; Kanna, Vijay; Murugadoss, Kanakasabai (International Journal of Research in Medical Sciences, 2016)
Background: Supraclavicular brachial plexus block is used commonly for upper limb orthopedic procedures. Among the adjuvants used to improve the quality of block induced by bupivacaine the alpha 2 agonists are of new interest. This study was done to compare dexmedetomidine and clonidine as adjuvants to bupivacaine for supraclavicular brachial plexus block in upper limb orthopedic surgeries. Methods: 60 ASA I/II patients aged between 20 and 50 years undergoing upper limb orthopedic procedures were selected and divided into two groups of 30 each. Group C received 35 ml of 0.375% Bupivacaine and clonidine 2µg/kg while Group D received 35 ml of 0.375% bupivacaine and dexmedetomidine 2 µg/kg. Onset time to sensory and motor blockade, vitals, complete duration of motor and sensory block, total duration of analgesia and side effects were noted. Results: The mean time of onset for sensory block and motor block in Group D was lower when compared to Group C. Except at 5th minute the pulse rate and mean arterial pressure were lower in Group D when compared to Group C. The mean time for total duration of sensory block and motor block was more in Group D when compared to Group C. The total duration of analgesia was higher in Group D than in Group C. Conclusions: The addition of dexmedetomidine to bupivacaine during supraclavicular brachial plexus block produces a shorter onset of time to sensory and motor block with prolonged duration of analgesia when compared to clonidine added to bupivacaine.